Parallel DNA Sequencing using Exact String-Matching Algorithms for Multiple Patterns - Terzic, Dzenana; Pita, Naida; Becirspahic, Nejla; Muhic, Dzenis (International Conference in Information, Communication and Automation Technologies (Online), 2025)
String matching algorithms are used to find specific patterns within a larger file or sequence. They are extensively used in bioinformatics, molecular biology, and information retrieval. With the world of data at our fingertips, the aim is to accelerate its processing. This study focuses on applying two distinctive parallel approaches to multiple substring matching in DNA. A Brute Force and FM Index algorithm are implemented, and their strengths and weaknesses are discussed based on experiments conducted on real genome sequences.